Hubungan Faktor Risiko dengan Kejadian Penyakit Kusta di Kota Kupang Tahun 2018 - Novita Scolastica Amsikan; Yuliana Radja Riwu; Deviarbi Sakke Tira (Universitas Nusa Cendana, 2019)
Leprosy is a disease caused by The mycobacterium leprae which has a 2-5 year incubation period that attack The skin, peripheral nerves, upper respirator mucosa and eyes. The number of leprosy cases in Kupang experienced fluctuatuions where Three were 63 cases in 2013, 61 cases in 2014, 74 cases in 2015 and 66 cases in 2016. The purpose of this Study has to analyze the riskf ractors associated with the incidence of leprosy in Kupang in 2018. The type of research used was an analytical survei using the Case Control desing. The Population in this Study were 66 people, with a Case sampel of 23 people and a Control sampel of 46 people, a total sampel of 69 people. The sampling technique used was simpel random sampling. The statistical test used was the Chi Square Test. The Results of the analysis showed that room temperatur factors had a significal relationship with the incidence leprosy with a P value of 0.002 (P<0,05) while knowledge, personal hygiene, length of contact, humidity, occupancy density did not have signifikan relationship with the incidence of leprosy. Suggestions for health institutions is that the should provide more comprehensive and sustainable education to the community in order to increase the knowledge about leprosy and the community should participate in conseling about leprosy and be able to participate in the prevention of leprosy.